Trade Disclosure Regulation in Markets with Negotiated Trades - Naik, Narayan Y.; Neuberger, Anthony; Viswanathan, S. (Review of Financial Studies, 1999)
In dealership markets disclosure of size and price of details of public trades is typically incomplete. We examine whether full and prompt disclosure of public-trade details improves the welfare of a risk-averse investor. We analyze a model of dealership market where a market maker first executes a public trade and then offsets her position by trading with other market makers. We distinguish between quantity risk and price revision risk. We show that if the market maker learns some information about the motive behind public trade, neither regime is unambiguously welfare superior. This is because greater transparency improves quantity risk sharing but worsens price revision risk sharing.